DESENTRALISASI DAN KEMANDIRIAN KELEMBAGAAN LOKAL (Peranan LMDH Gandong Kabupaten Ngawi dalam Pengelolaan Jaminan Layanan Kesehatan Masyarakat Desa Hutan serta Penanganan Konflik Pelanggaran Hak Cipta oleh Asosiasi Pengrajin Cor Patung Kuningan Bejijong Ka - Erviantono, Tedi (Jurnal Interaktif, 2010)
In practical level, decentralisation has strengthened social capital of local community to solve their problems. The freedom for creating self-organised association increases the capability of local people to influence local policy, such as JPKMDH (Jaminan Pemeliharaan Kesehatan Masyarakat Desa Hutan) programme done by LMDH (Lembaga Masyarakat Desa Hutan) Gandong, Kabupaten Ngawi. Morever, that capability has also protected their economic interests when competing with global market. It can be seen from the implementation of Village Regulation No. 6/2008. That regulation is a clear example on how local government and local people work together to protect their interest to face the implementation of free market. For two examples explained above, the writer argues that the establishment of local institution created by local people can be used to mediate and facilitate the relation between local government and its citizen. However, it needs a strong sense of trust among local goverment and its citizen.Key words: Desentralisation, Social Capital, Local Institutions